2018
DOI: 10.1016/j.procs.2018.04.112
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Middleware-based IoT Applications through Run-Time Pluggable QoS Management Mechanisms. Application to a oneM2M compliant IoT Middleware

Abstract: In the recent years, telecom and computer networks have witnessed new concepts and technologies through Network Function Virtualization (NFV) and Software-Defined Networking (SDN). SDN, which allows applications to have a control over the network, and NFV, which allows deploying network functions in virtualized environments, are two paradigms that are increasingly used for the Internet of Things (IoT). This Internet (IoT) brings the promise to interconnect billions of devices in the next few years rises severa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Ouedraogo et al [150] suggested an answer for QoS management of the IoT-based HetNet scenario. The authors show a significant interest in expanding network functions through traffic-made middleware-oriented applications.…”
Section: Infrastructural Applicationsmentioning
confidence: 99%
“…Ouedraogo et al [150] suggested an answer for QoS management of the IoT-based HetNet scenario. The authors show a significant interest in expanding network functions through traffic-made middleware-oriented applications.…”
Section: Infrastructural Applicationsmentioning
confidence: 99%
“…The oneM2M standard-based IoT platforms have shown its practical feasibility in developing home appliances [25], smart farm [26], smart office [27], medication [28], and semantic interworking in smart cities [29,30]. Recently, Ouedraogo et al considered the quality of service (QoS) required by the IoT applications as scientific challenges, and then presented a solution consisting of the dynamic, autonomous and seamless deployment of QoS management mechanism integrated with an oneM2M standard-based IoT middleware [31]. Zhao et al proposed an oneM2M-complaint stacked middleware to integrate open-source hardware and software projects for IoT development and research [32].…”
Section: Iot Middleware and Onem2m Standardmentioning
confidence: 99%
“…The literature corpus after application of all filters includes 31 articles. The contents of these studies are further analyzed to identify the main focus of the studies, which are:Patient monitoring: [38,39,40,41,42];Device integration and data interoperability: [43,44,45,46,47,48,49];Smart hospitals: [50,51,52];Operating Room monitoring (Intelligent OR): [18,19,20,21,22,23,24,25,26,27,28];QoS-Aware Middlewares: [53,54,55,56,57]. …”
Section: Related Workmentioning
confidence: 99%
“…Their strategy consists of migrating clients connections of Edge Computing applications to closer brokers. In the studies [55] and [54], the authors propose the addition of QoS management modules. The strategy adds a communication layer on top of protocols such asHTTP (Hypertext Transfer Protocol), COaP (Constrained Application Protocol) and MQTT (Message Queuing Telemetry Transport).…”
Section: Related Workmentioning
confidence: 99%